THE STUDENTS’ CHALLENGES IN TRANSLATING IDIOMATIC EXPRESSIONS IN THE NOVEL ‘LASKAR PELANGI’: A DESCRIPTIVE STUDY OF TRANSLATION FROM INDONESIAN TEXT INTO ENGLISH - Martina Mulyani; Asep Taufik Ardiansyah (English Education Department of STKIP Pasundan, 2020)
There are some problems commonly faced by a translator, one of them is culture. This problem usually emerges when translating literary works. So far, many of the researches mostly use texts in which English becomes the source language and only a few takes English as the target language. This research attempts to investigate the challenges in translating Indonesian text into English especially idiomatic expression. 20 juniors in tertiary level education got involved in this research. They were asked to translate a novel from Andrea Hirata entitled Laskar Pelangi. The investigation on the products of their translations revealed that the students encountered some problems concerning accuracy, readability and acceptability. The result from interview showed that the students difficulties arose from students’ lack of understanding of target language grammatical rules, and inability to find a target language equivalent are the main reasons of the student’s difficulties. So as to the strategies to deal with these difficulties, the students employed some strategies such as consulting dictionaries, paraphrasing, and using word-for-word and literal translation. Such strategies seemed to be in adequately cope with the cultural issue, so it is suggested that the students familiarize themselves with their own culture, and English culture by reading more books, and watching Indonesian as well as English series and films. Moreover, being familiar with the adopted strategies, the students can translate literary works more properly.